119 A Meta-Regression Analysis to Evaluate the Influence of Branched-Chain Amino Acids in Lactation Diets on Sow and Litter Growth Performance. (12th April 2022) - Holen, Julia P; Tokach, Mike D; Woodworth, Jason C; DeRouchey, Joel M; Gebhardt, Jordan T; Titgemeyer, Evan C; Goodband, Robert D
Abstract: The branched-chain amino acids (BCAA) Ile, Leu, and Val are 3 dietary essential amino acids for lactating sows; however, effects of dietary BCAA on sow and litter growth performance in the literature are equivocal. Thus, a meta-regression analysis was conducted to evaluate effects of BCAA and their interactions in lactating sow diets to predict litter growth performance, sow bodyweight (BW) change, and sow feed intake. Thirty-four publications representing 43 trials from 1997 to 2020 were used to develop a database that contained 167 observations. Diets for each trial were reformulated using NRC (2012) nutrient loading values in an Excel-based spreadsheet. Amino acids were expressed on a standardized ileal digestible (SID) basis. Regression model equations were developed with the MIXED procedure of SAS (Version 9.4, SAS Institute, Cary, NC), and studies were weighted by the inverse of the squared SEM. Statistically significant ( P < 0.05) predictor variables were assessed with a step-wise manual forward selection and required to provide an improvement of at least 2 BIC for model inclusion. Significant predictor variables within 3 equations developed for litter ADG included the count of weaned pigs per litter, dietary concentrations of NE, SID Lys, and CP, sow ADFI, Val:Lys, Ile:Lys, and Leu:Val. For sow BW change, significant predictor variables within 2 developed models included litter size at 24 h, sow ADFI, Leu:Lys, and Ile+Val:Leu. The optimum equation for sow ADFI included Leu:Trp, SID Lys, NE, CP, and Leu:Lys as significant predictor variables. Overall, the prediction equations suggest that BCAA have an important role in litter growth, sow BW change, and feed intake during lactation; however, the influence of BCAA on these criteria is much smaller than that of other dietary components such as NE, SID Lys, sow ADFI, and CP.